Pathological analysis of the prostatic anterior fat pad at radical prostatectomy: insights from a prospective series. (30th September 2016) - Ball, Mark W.; Harris, Kelly T.; Schwen, Zeyad R.; Mullins, Jeffrey K.; Han, Misop; Walsh, Patrick C.; Partin, Alan W.; Epstein, Jonathan I.
Abstract : Objective: To assess factors associated with lymphatic drainage and lymph node (LN) metastasis to the prostatic anterior fat pad (PAFP) in men with prostate cancer and the utility of routine PAFP analysis at the time of radical prostatectomy (RP). Patients and Methods: Our institution began to prospectively collect PAFP tissue in 2010. The PAFP was removed at the time of RP and sent as a pathological specimen separate from the pelvic LNs and prostate. Consecutive RPs performed at our institution in which the PAFP was removed were reviewed to determine the rate of LNs in the PAFP, the rate of metastatic LNs in the PAFP, and the association of metastatic PAFP LN with clinical and pathological features. The impact on biochemical recurrence (BCR) was assessed with a Cox's proportional hazard model. Results: In all, 2 413 PAFP specimens were available for analysis. LNs were found in the PAFP in 255 (10.6%) cases and metastatic LNs in the PAFPs were found in 14 (0.6%) cases. Metastatic PAFP LNs were associated with anterior tumours in 11 of the 14 cases ( P = 0.01), and were present only in preoperative D'Amico intermediate‐ (six of 14) and high‐ (eight of 14) risk patients ( P < 0.001). Metastatic PAFP LNs were associated with extraprostatic disease in 13 of the 14 cases, although concomitant pelvic LN involvement was present in only four of the 14 cases. With a mean follow‐up of 1.5 years, three of the 14 patients with metastatic PAFP LN developed BCR. Positive LN involvement in either the pelvic LN or PAFP had worse BCR than LN‐negative patients ( P < 0.001); however, there was no difference in BCR between patients with positive pelvic LN and positive PAFP LN ( P = 0.5). Conclusion: Metastatic PAFP LNs are rare and always occur in the presence of other adverse pathological features. The routine pathological analysis of PAFP as a separate specimen, especially in low‐risk disease, may not be warranted.